Urban growth trends in Riyadh (2020 – 2010 – 2000 –1984) - Ain, Jumah Ibrhim; Nahhas, Faten Hamed (Journal of natural sciences, life and applied sciences, 2021)
Identifying urban growth trends contributes to sound decision-making, planning and clear scenarios for future development (Altwaijri, 1438-AH). The research uses the techniques of remote sensing and geographic information systems (GIS) to study the urban growth of Riyadh from the first nucleus until 2020 and to determine the growth trends, causes and physical areas that arose during this period. Space images were used and analyzed by the USGS and Google Earth program using ArcGIS Desktop 10.8. The city’s initial growth was in the area around Safa Square and the surrounding area, which developed through various stages of history, especially after it became the capital of Saudi Arabia and experienced rapid development from 2000 to 2020. The study came in two chapters, the first on about the stages of development and evolution for Riyadh, then the second chapter, to analyze the satellite images to show the trends of the city’s development over the last twenty years, followed by the conclusions and recommendations.